Comparative study on CI engine performance and emissions using a Novel Antioxidant Additive / N Kapilan - N, Kapilan (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2020)
The depletion of conventional energy sources and environmental pollution related to use of these energy sources make biodiesel as a renewable replacement to diesel. The biodiesel can be used as an immediate replacement to fossil diesel as its properties are comparable to diesel. The main drawback of the biodiesel is its lower oxidation stability and prone to microbial growth which degrades the properties of biodiesel during storage. However, these problems can be overcome by adding suitable additives to the biodiesel. The non-edible neem oil is one of the feedstocks used for biodiesel in India. The neem biodiesel has lower oxidation stability and hence it is necessary to add suitable additive. The eucalyptus oil has better antioxidant and microbial inhibition properties and hence it was used as an additive in this work. The effect of adding this additive on the biodiesel properties, engine emissions and performance were studied. The engine tests were conducted on a compression ignition engine at different loads with various concentration of eucalyptus oil. The engine performance indicates that the thermal efficiency of the engine with biodiesel is lower than the diesel fuel while the engine exhaust emissions like HC, CO and smoke were lower with the biodiesel. The use of eucalyptus oil as an additive to the biodiesel at full load increases the engine thermal efficiency by 3.08%. Also, it lowers the engine exhaust emissions except NOx emission.